A narrative review of antithrombin use during veno-venous extracorporeal membrane oxygenation in adults: rationale, current use, effects on anticoagulation, and outcomes. (September 2020) - Piacente, Claudia; Martucci, Gennaro; Miceli, Vitale; Pavone, Gaetano; Papeo, Anna; Occhipinti, Giovanna; Panarello, Giovanna; Lorusso, Roberto; Tanaka, Kenichi; Arcadipane, Antonio
Background: During extracorporeal membrane oxygenation, the large contact surface between the blood and the extracorporeal circuit causes a continuous activation of coagulation and inflammation. Unfractionated heparin, a glycosaminoglycan that must bind to antithrombin as a cofactor, is currently the standard anticoagulant adopted during extracorporeal membrane oxygenation. Antithrombin, beyond being a potent natural anticoagulant, acts in the cross-talk between coagulation and inflammatory system through anticoagulation and coagulation-independent effects. Objectives: In this review, we describe, in the adult setting of veno-venous extracorporeal membrane oxygenation, the pathophysiological rationale for antithrombin use, the current practice of administration, and the effects of antithrombin on anticoagulation, bleeding, and outcomes. Data sources: Studies on adults (18 years or older) on veno-venous extracorporeal membrane oxygenation published from 1995 to 2018 in order to evaluate the use of antithrombin. Results: In adults on veno-venous extracorporeal membrane oxygenation, antithrombin supplementation has a highly pathophysiological rationale since coagulation factor consumption, systemic inflammatory response syndrome, and endothelial activation are triggered by extracorporeal membrane oxygenation. Eleven articles are focused on the topic but among the authors there is no consensus on the threshold for supplementation (ranging from 70% to 80%) as well as on the dose (rarely standardized) and time of administration (bolus vs continuous infusion). Consistently, antithrombin is considered able to achieve better anticoagulation targets in or not in the presence of heparin resistance. The impact of antithrombin administration on bleeding still shows contrasting results. Conclusion: Antithrombin use in veno-venous extracorporeal membrane oxygenation should be investigated on the threshold for supplementation, dose, and time of administration.